Household Financial Planning in Achieving a Balanced Budget - Endah Masrunik; Suprianto Suprianto; Henni Indariyanti; Arif Wahyudi (JASF: Journal of Accounting and Strategic Finance, 2024)
Financial planning is like a map that determines the direction of family finances. The unmet needs of a family are often not due to a small income but due to expenses that are often uncontrollable. This research aims to find out the application of household financial planning to achieve the principle of a balanced budget. This research uses a qualitative method with a case study approach. The data collection was done by observation, direct interview, and documentation. The location of this research is the informant's residence within the scope of Sananwetan Subdistrict, Blitar City. The results of this study show that housewives plan their finances every month. The planning done is based on the previous month's records. The decision-making practices carried out by housewives to determine financial allocations are not necessarily decided by themselves, but they involve their husbands and other family members to deliberate to produce the best solution. To achieve budget balance, awareness is needed to prioritize primary needs and pay attention to lifestyle. These results implied that families can pay more attention to health insurance and investment aspects so that expenses become equivalent to income or a balanced budget. Therefore, this research not only enriches literature related to household financial management but also opens up new insights for financial practitioners and family consultants in developing more comprehensive financial literacy programs so that they can sustainably improve household financial welfare.